Physical, chemical and Bacteriological Evaluation of The Quality of Raw Sheep Milk in The City of Salamiyah and its Countryside (Journal of Hama University, 2024)
This This research was conducted in the laboratories of the Directorate of Internal Trade and Consumer Protection in Hama, with the aim of studying the physical, chemical and bacterial quality of 8 samples of raw sheep milk, which were collected from the city of Salamiyah and its countryside, with the aim of identifying the type and quality of the milk and the extent of tampering and adulteration that may occur in the milk sold, by conducting Physical analyzes (such as appearance, taste, smell, and density) and chemical analyzes as percentages (protein, fat, lactose, non-fat solids, and acidity), as well as bacterial analyzes (general counts, total coliforms, and E. coli). The results showed that the physical properties, such as appearance, smell, taste, and density, were acceptable in most of the samples studied, with the exception of two samples that had impurities, 3 samples that had an unacceptable taste, and 3 samples that had low density. As for the chemical properties, a decrease in the percentage of fat and lactose sugar and a slight increase in total protein was observed, where their percentages ranged Between 3.40-8.8%, 3.40-5.31%, and 4.2-8.1% respectively, and also a decrease in the percentage of non-fatty solids, which reached 8, and an increase in the acidity percentage, which reached 0.21%, which is in violation of the Syrian standard. While an increase in bacterial indicators was observed, the results confirmed the presence of large numbers of total microorganisms in one milliliter of raw milk, with the number falling between 1.1 x 410 and 3.6 x 810 cells/ml. The results also confirmed the presence of large numbers of coliform bacteria, as their numbers changed between 4.8 x 310 and 4.6 x 610 cells/ml, as well as for Escherichia coli between 8.2 x 110 and 6.3 x 410 cells/ml. We conclude from the study that milk It is in violation of the Syrian standard, which constitutes a major concern for public health and society.